1990
DOI: 10.2151/jmsj1965.68.5_523
|View full text |Cite
|
Sign up to set email alerts
|

Westerly Wind Bursts and Surface Heat Fluxes in the Equatorial Western Pacific in May 1982

Abstract: This paper presents a case study of westerly wind bursts in the equatorial western Pacific (EWP) during May 1982. Using 12-hourly island, atoll, and ship observations, the latitudinal extent of the 11-day long burst was determined to be within about five degrees from the equator, whereas its longitudinal domain varied considerably, raging from 1000 km when the burst was first recognized to more than 3500 km when the burst was fully developed. Consequently, Rossby numbers changed appreciably throughout the burs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…For westerly wind regimes, the enhanced surface heat fluxes favors the growth of convective clouds, which in turn decreases the heights of mixed layers, as illustrated previously. This result also is in good agreement with estimates of surface heat fluxes in the equatorial western Pacific in May 1982 (Chu and Frederick, 1990). They found that the latent heat flux tripled from the pre-burst period to the burst period of westerly wind and plummeted afterward.…”
Section: Bulk Fluxessupporting
confidence: 86%
“…For westerly wind regimes, the enhanced surface heat fluxes favors the growth of convective clouds, which in turn decreases the heights of mixed layers, as illustrated previously. This result also is in good agreement with estimates of surface heat fluxes in the equatorial western Pacific in May 1982 (Chu and Frederick, 1990). They found that the latent heat flux tripled from the pre-burst period to the burst period of westerly wind and plummeted afterward.…”
Section: Bulk Fluxessupporting
confidence: 86%
“…This figure shows that the wave during June-July 1982 was followed by gradual eastward progression of anomalously active convection and the development of mature El Niño conditions. Chu and Frederick (1990) describe an intense westerly wind burst during mid- May 1982. The solid gray line in Fig.…”
Section: Activity Indexmentioning
confidence: 97%
“…The surface LHF may be calculated according to the following bulk formula (Weare et al 1981;Chu and Frederick 1990):…”
Section: A Ssv Contribution To the Intraseasonal Lhfmentioning
confidence: 99%